Collaboration and innovation: the E-Fan X - Vincent, Kellie (Henry Stewart Talks, 2022)
This case study examines the E-Fan X hybrid-electric flight demonstrator, a joint project between Airbus, Rolls-Royce, and Siemens. An example of collaborative innovation, though the project in itself failed, it resulted in significant advancements and innovations that nevertheless demonstrated the importance of such collaborations.